1999
DOI: 10.1097/00006534-199912000-00053
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Permanent Magnetic Field Therapy on Wound Healing in Suction Lipectomy Patients: A Double-Blind Study

Abstract: In summary, we think that the intradermal injection of the tumescent solution with epinephrine, which produced a peau d'orange appearance of the overlying skin, resulted in superficial flap loss secondary to the vasoconstrictive property of epinephrine combined with the hydrostatic pressure of the injection in this patient within a superficial plane and flap elevation. This delayed the clearance of epinephrine from the flaps. In this case, removal of the sutures did not result in any improvement in the flap, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 10 publications
1
26
0
Order By: Relevance
“…It is also clear that cells undergoing tumorigenesis have been observed to have altered cytoskeletons with enhanced motility and less polarity [30][31]. Similar effects were also observed in migrating cells during many biological processes, such as tissue repair and regeneration [1], [2], [18], [19]. All of these cytoskeletal dynamics of migrating cells are highly associated with the EGFR signal pathway because there is intensive cross talk between the cytoskeleton and the EGFR signal pathways.…”
Section: Discussionmentioning
confidence: 76%
“…It is also clear that cells undergoing tumorigenesis have been observed to have altered cytoskeletons with enhanced motility and less polarity [30][31]. Similar effects were also observed in migrating cells during many biological processes, such as tissue repair and regeneration [1], [2], [18], [19]. All of these cytoskeletal dynamics of migrating cells are highly associated with the EGFR signal pathway because there is intensive cross talk between the cytoskeleton and the EGFR signal pathways.…”
Section: Discussionmentioning
confidence: 76%
“…[Eccles, 2005;Salomonowitz et al, 2011]. Several studies have reported that SMF can reduce patients' pain sensitivity, and reduce pain of various diseases, such as, all chronic pain [Brown et al, 2002;Langford and McCarthy, 2005;Kanai et al, 2011], osteoarthritis pain [Segal et al, 2001;Harlow et al, 2004;Wolsko et al, 2004], neuropathic pain [Weintraub et al, 2003], and postoperative pain [Man et al, 1999]. Except for clinical trials, animal experiments have also been performed to prove analgesia effects of SMF [Antal and Laszlo, 2009;Laszlo and Hernadi, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…Biophysical forces such as electromagnetic fields (EMFs) and static magnetic field (SMF) have attracted interest for their effects on bone remodeling 18,19 and wound healing, [20][21][22] and have been used as adjuvant treatments for cartilage regeneration. [23][24][25][26][27][28][29][30][31] For example, EMFs apparently stimulated chondrocyte proliferation and proteoglycan synthesis in bovine and human cartilage cells.…”
Section: Introductionmentioning
confidence: 99%